0273 Sleep Disorders as a Potential Risk Factor for Dementia in Elderly Adults. (25th May 2022) - Kuhler, Cassandra; Wills, Chloe; Mason, Brooke; Tubbs, Andrew; Seixas, Azizi; Turner, Arlener; Jean-Louis, Girardin; Killgore, William; Grandner, Michael
Abstract: Introduction: Sleep disorders such as insomnia are seen in the early onset of Alzheimer's disease, the most common form of dementia. Simultaneously, sleep disorders may indicate increased risk for the development of dementia. Due to the rate of comorbidity of these two conditions seen in the elderly population, the relationship between dementia and sleep disorders is a topic of interest for researchers. A bidirectional correlation between the two could have important implications in the clinical field exploring factors that lead to dementia Methods: Data was assessed from 17, 146 older adults from the 2018 Health and Retirement Survey. Participants were surveyed using questionnaires regarding both incident dementia or serious memory impairment in the past 2 years and the presence of a sleep disorder, as diagnosed by a doctor or health professional. Those who reported no dementia in the previous wave (N=16, 547) were asked if they had been diagnosed since they were last asked. N=185 individuals reported incident dementia in the 2-years between assessments. Responses were coded to either "Yes" or "No". A Poisson regression analysis was conducted to explore the relationship between incident dementia and sleep disorders. Results: In a sample of older adults, unadjusted results indicate that having a sleep disorder was associated with a 0.6% increased risk of new onset dementia (PRR=1.006; 95%CI[1.001, 1.012]; p=0.026). These results were sustained when adjusted for sex, age, race, ethnicity, and depression (PRR=1.006; 95%CI[1.001, 1.012]; p=0.013). Conclusion: Chronic sleep disturbances may be a factor used to indicate increased risk for dementia and help with early detection of the disease. These results demonstrate the value of sleep disorders screening among those at risk for dementia. Further research is needed to clarify these findings (e.g., explore specific sleep disorders) and expand the follow-up window (i.e., beyond 2 years). Support (If Any): The HRS (Health and Retirement Study) is sponsored by the National Institute on Aging (grant number NIA U01AG009740) and is conducted by the University of Michigan.